2017
DOI: 10.1016/j.celrep.2017.11.051
|View full text |Cite
|
Sign up to set email alerts
|

Primary Patient-Derived Cancer Cells and Their Potential for Personalized Cancer Patient Care

Abstract: SummaryPersonalized cancer therapy is based on a patient’s tumor lineage, histopathology, expression analyses, and/or tumor DNA or RNA analysis. Here, we aim to develop an in vitro functional assay of a patient’s living cancer cells that could complement these approaches. We present methods for developing cell cultures from tumor biopsies and identify the types of samples and culture conditions associated with higher efficiency of model establishment. Toward the application of patient-derived cell cultures for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
157
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(172 citation statements)
references
References 27 publications
5
157
0
1
Order By: Relevance
“…Studies that report normal epithelial cell expansion have tended to initiate culture from early‐stage primary NSCLC tumors, whereas studies in which cancer cells have been expanded have initiated culture using biopsies or effusions from patients with late‐stage, therapy‐resistant disease7, 8, 9 or from PDX models,24 which may be more aggressive and/or more adaptable to cell culture. This would be consistent with traditional NSCLC cell culture methods and PDX models, where patient models are more readily established from late‐stage, metastatic or therapy‐resistant disease than from early‐stage primary disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies that report normal epithelial cell expansion have tended to initiate culture from early‐stage primary NSCLC tumors, whereas studies in which cancer cells have been expanded have initiated culture using biopsies or effusions from patients with late‐stage, therapy‐resistant disease7, 8, 9 or from PDX models,24 which may be more aggressive and/or more adaptable to cell culture. This would be consistent with traditional NSCLC cell culture methods and PDX models, where patient models are more readily established from late‐stage, metastatic or therapy‐resistant disease than from early‐stage primary disease.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that adult human lung fibroblasts do not support long‐term normal airway epithelial cell expansion in the same way as 3T3‐J2 cells17 so the use of adult and/or human feeder cells might favor tumor cell expansion. Relevant biological differences might also exist between mitotic inactivation using irradiation4, 9 rather than mitomycin C, as used here. Alternatively, different tissue acquisition methods,9 feeder cell‐conditioned medium,10, 27 low oxygen,10 harsh tissue digestion protocols26 and/or initially serum‐starving cells6 might help to select tumor cells by inducing differentiation or apoptosis in normal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the decades, the development of high throughput and quantitative approaches to these assays has resulted in their widespread adoption as reliable assays for cell motility (4,5). One such application is the assessment of motility, proliferation, and drug response within short term ex vivo cultures of human cancers-an emerging approach for developing personalized therapeutic strategies (6,7). However, for some applications, these approaches are limited due to their requirement for culturing cells in conditions that deviate from those of routine culture and their reliance on measuring population averages.…”
mentioning
confidence: 99%
“…However, for some applications, these approaches are limited due to their requirement for culturing cells in conditions that deviate from those of routine culture and their reliance on measuring population averages. One such application is the assessment of motility, proliferation, and drug response within short term ex vivo cultures of human cancers-an emerging approach for developing personalized therapeutic strategies (6,7). For this approach, assessing the behaviors of each cell in a heterogeneous population shortly after explant, without sacrificing the integrity of the culture, is ideal.…”
mentioning
confidence: 99%